Herbaceous biomass–species diversity relationships in nutrient hotspots of a semi-arid African riparian ecosystem - van Coller, Helga; Siebert, Frances (African journal of range & forage science, 2015)
The hump-back relationship between species diversity and productivity predicts highest species richness at intermediate levels of biomass, and low species numbers in least and most productive habitats. Sodic patches of semi-arid savannas are considered ‘nutrient hotspots’ by producing high-quality forage. The impact of biomass reduction (due to overgrazing) and accumulation (in the absence of herbivores) on herbaceous species richness and diversity is still unknown for these hotspots. We tested the relationship between biomass and herbaceous species richness/diversity in savanna sodic sites across varying biomass levels obtained through different herbivore exclosures. LOWESS and quadratic regression analyses revealed a unimodal species richness/ diversity–biomass relationship for biomass <2 500 kg ha−1. Species richness and diversity in the sodic zone peaked at 1 300 kg ha−1, followed by a steady decline. At biomass levels exceeding 2 500 kg ha−1, i.e. where herbivores have been excluded for 10 years, the decline in species richness and diversity stabilised. Despite many debates surrounding unimodal relationships and the intermediate disturbance hypothesis, this study confirmed a peak in species richness and diversity at intermediate biomass levels in a herbivory-adapted ecosystem. Herbivores drive ecosystem heterogeneity and enhance herbaceous species richness and diversity by keeping biomass at intermediate levels (i.e. <2 500 kg ha−1 for this sodic site).